2014
DOI: 10.1073/pnas.1400378111
|View full text |Cite|
|
Sign up to set email alerts
|

Host adaptation to viruses relies on few genes with different cross-resistance properties

Abstract: Significance Despite ample knowledge of the genetics and physiology of host responses to parasites, little is known about the genetic basis of host adaptation to parasites. Moreover, adaptation to one parasite is likely to impact the outcome of different infections. Yet these correlated responses, seminal to the understanding of host evolution in multiparasite environments, remain poorly studied. We determined the genetic and phenotypic changes underlying adaptation upon experimental evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
208
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(220 citation statements)
references
References 49 publications
5
208
0
Order By: Relevance
“…2011, 2012; Martins et al . 2014). The other group of natural parasites that is well‐studied in D. melanogaster is parasitoid wasps, and here, a few major‐effect loci control resistance (Poirie et al .…”
Section: Discussionmentioning
confidence: 99%
“…2011, 2012; Martins et al . 2014). The other group of natural parasites that is well‐studied in D. melanogaster is parasitoid wasps, and here, a few major‐effect loci control resistance (Poirie et al .…”
Section: Discussionmentioning
confidence: 99%
“…It could be expected that tradeoffs in the adaptation to distantly related plants would enable speciation via host shift (17). However, recent experimental studies question the existence of such tradeoffs in the evolution of both parasites (38) and hosts (44). In fact, the evolution of new parasite species by host shifts has been found to be overestimated (13) or predominantly allopatric (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that insect susceptibility to viral infection is determined by host factors, which either facilitate (6,7) or restrict viral replication (8)(9)(10). In addition, the bacterial flora, particularly endosymbiotic Wolbachia strains, modifies susceptibility to viral infections (11,12).…”
mentioning
confidence: 99%